Adolescents’ sexual education in women’s opinion treated in outpatient health care centers - Robak-Chołubek, Dorota; Bombolewska, Magdalena; Chołubek, Magdalena; Wiktor, Henryk (Nursing in the 21st Century, 2011)
Introduction. Many adolescents are confronted at some point during their teen years with choices about whether or not to have sex. Many factors affect those choices. Parents, educators, and other adults working with youth have learned that they cannot directly control the sexual behavior of teens. Adults have often own opinion on sexual education of youth.Aim. This research has been carried out to present adolescents’ sexual education in women’s opinion from health care centers in LublinMaterial and methods. The investigations were carried out on women from health care centers in Lublin. One hundred and fifty voluntarily and anonymously completed questionnaires have been analyzed using Statistica program. Any correlation found has been validated using χ2 test.Results. About 2/5 questioned estimated the level of sexual education as bad. Women with higher education more often estimated it negatively in comparison to women with lower education. Childless women more often prefer sexual education in mixed groups (co-educational) in relation to those, who possess children as well as to those with higher and secondary education.Conclusions. Additional investigations are necessary to credibly estimate the view of adults to the influence of sexual education on behavior of adolescents.